Patient and professional use of the root coverage esthetic score (RES) and how it relates to patient satisfaction following periodontal plastic surgery - Anne Judith Sørdahl; Anders Verket (BMC, 2022)
Abstract Background Following periodontal plastic surgery in the treatment of recession defects, previous studies have reported that patients rate the esthetic outcomes more favorable than dental professionals. The root coverage esthetic score has been developed and suggested to serve as a comprehensive assessment instrument as it addresses several esthetic outcomes following root coverage procedures. However, no study has yet reported on patient use of this instrument. In the present study clinical, esthetic and patient-reported outcomes following periodontal plastic surgery were assessed. The primary objective was to compare the esthetic/clinical outcome as judged by the patient and by one dentist by using the root coverage esthetic score. The secondary objective was to evaluate the correlation between patient-reported outcomes, root coverage esthetic score and clinical parameters following treatment of recession defects. Materials and methods Subjects that had undergone periodontal plastic surgery were invited to score the treatment outcome according to the root coverage esthetic score, which subsequently also was professionally scored by a dentist. Thereafter, the subjects answered a questionnaire on patient satisfaction. All types of surgical root coverage procedures in canine or incisor teeth were included. Results A total of 34 subjects were included, presenting 46 treated recessions. No statistically significant different score was found comparing the root coverage esthetic score by the patient and the professional. The majority of subjects was satisfied with the treatment outcome, and most would have undergone the treatment again. Conclusion The root coverage esthetic score assessment can be conducted by patients and was not statistically significant different to that of the professional. Patient satisfaction is not always dependent on complete root coverage or the other clinical parameters included in the root coverage esthetic score.